CHALLENGES FACED BY EFL UNIVERSITY STUDENTS IN ONLINE ENGLISH SPEAKING CLASSES AT VINH UNIVERSITY DURING THE COVID-19 PERIOD - Le Thi Tuyet Hanh*, Nguyen Dao Tien (Tạp chí Khoa học, 2024)
During the Covid-19 pandemic, many universities switched rapidly to the online learning mode to maintain the continuity of the teaching and learning process. This explanatory mixedmethods study was an attempt to investigate the problems EFL students encountered in their online English speaking classes. The study involved 135 EFL students at Vinh University, a key national university in Vietnam. To collect data, a questionnaire and semi-structured interview were used. The results showed that there were six barriers that influenced EFL students’ speaking skills in online classes, including facilities, computer skills, coordination, teaching method, learners’ attitudes and assessment. From the findings, the study tried to suggest some pedagogical solutions in order to improve the quality of online English speaking learning for EFL university students